The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1063/5.0073818
|View full text |Cite
|
Sign up to set email alerts
|

Measurement method of natural frequencies and tension forces for cables based on elasto-magnetic sensors calibrated by frequencies

Abstract: Vibration-based (VB) method and elasto-magnetic (EM) method are usually used to measure cable forces of cable-supported bridges. For the VB method, it is difficult to accurately identify each order natural frequency of the cable disturbed by random excitations, and there are also no precise selection criteria between the taut string model and the hinged beam model. For the EM method, it is not convenient to calibrate EM sensors on bridges in service due to unknown cable forces. To address these issues, a vibra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In this study, Equation ( 14) was used to calculate the cable force of a cable-stayed cable, and the influence of the bending stiffness was not considered in the calculations. In order to reduce the deviation between the calculated cable force and the measured cable force, the bending stiffness of the 12 cables mentioned above was corrected according to Equation (15) in Section 3.4, and the calculations are shown in Table 7. After the coefficient correction, it was found that when the cable was long, the influence of the bending stiffness on the accuracy of the measured cable force was almost zero and could be ignored.…”
Section: Analysis Of the Influence Of Bending Stiffness On The Calcul...mentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, Equation ( 14) was used to calculate the cable force of a cable-stayed cable, and the influence of the bending stiffness was not considered in the calculations. In order to reduce the deviation between the calculated cable force and the measured cable force, the bending stiffness of the 12 cables mentioned above was corrected according to Equation (15) in Section 3.4, and the calculations are shown in Table 7. After the coefficient correction, it was found that when the cable was long, the influence of the bending stiffness on the accuracy of the measured cable force was almost zero and could be ignored.…”
Section: Analysis Of the Influence Of Bending Stiffness On The Calcul...mentioning
confidence: 99%
“…Jo, Hyeon Cheol et al [14] proposed a tension and tension range evaluation method based on multiple digital images that was able to obtain the cable force more economically and efficiently than traditional methods could. Xiaofeng Liu et al [15] proposed a vibration-based elastic-magnetic (VBEM) method that had a good ability to identify the natural frequencies of each order of steel strand. Hongbo Liu [16] conducted dynamic response tests on closed cables and high vanadium cables under prestress and proposed a deep learning model that could intelligently identify the cable force for construction based on test data.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Joule effect and the magnetization theory of ferromagnetic material, there is a functional relationship between the stress of rebar and the change in magnetic permeability [30,31]. In Equation (1), µ is the permeability of rebar, µ 0 is the vacuum permeability, λ s is the axial deformation constant, M s is the saturation magnetization, K u is the uniaxial magnetic anisotropy constant, H R is the excitation magnetic field, and θ 0 is the angle between the magnetic field and the easy magnetization axis [32].…”
Section: Theorymentioning
confidence: 99%